Detection of Anaplasmataceae agents and co-infection with other tick-borne protozoa in dogs and Rhipicephalus sanguineus sensu lato ticks - Low, Van Lun; Prakash, Batah Kunalan; Lim, Yvonne Ai Lian; Tan, Tiong Kai; Siow, Vinnie Wei Yin; Sofian-Azirun, Mohd; AbuBakar, Sazaly (Springer, 2018)
Anaplasmosis and ehrlichiosis are of serious health concern worldwide for animals and humans. In the present study, we report the occurrence of Anaplasma platys and Ehrlichia canis in dogs and Rhipicephalus sanguineus sensu lato (s.l.) ticks from Peninsular Malaysia using a nested polymerase chain reaction assay based on amplification of the 16S rRNA gene. Anaplasma platys was detected from dogs and ticks with prevalence rates of 3.3% (8/240) and 2.9% (4/140), respectively. On the other hand, 12.9% (31/240) of the dogs and 0.7% (1/140) of the ticks were tested positive for E. canis. Additionally, co-infections of A. platys and E. canis with Babesia or Hepatozoon protozoa were also noted in this study. Double infection (E. canis + B. gibsoni) was observed in tick, whereas triple infections (E. canis + A. platys + B. vogeli and E. canis + A. platys + H. canis) were found in dogs. This study represents the first evidence of A. platys DNA in R. sanguineus s.l. in Malaysia.